Taking the Postal Business to the Sky with Information Technology - Putri Az-zahra; Maristiana Ayu (Journal of Creative Power and Ambition (JCPA), 2026)
The power of information technology lies in its ability to advance industries and revolutionize the way businesses operate. Numerous leading companies have harnessed information technology to rethink their business strategies. According to Law Number 11 of 2008 concerning Electronic Information and Transactions, the utilization of information technology plays a crucial role in trade and the national economic growth, aiming to improve the welfare of the population. Information technology, in essence, refers to a technique for collecting, preparing, storing, processing, disseminating, analyzing, and distributing information. In this study, a research methodology employing a qualitative approach supported by quantitative data and descriptive analysis techniques was employed. The findings of this study reveal that postal business operations are conducted by PT. Pos Indonesia and courier service companies. These enterprises have effectively leveraged information technology in the development of postal businesses. For instance, PT. Pos Indonesia has implemented online money transfer services, with transactions completed within minutes, along with trace and tracking services. Additionally, courier service companies have expanded their online services, utilizing SMS for tracking the progress of mail deliveries. The primary obstacle to the utilization of information technology is the substantial cost associated with establishing online networks and procuring equipment. From the perspective of postal service users, the public has already embraced information technology-based postal services.